Anti-trafficking Efforts and Colonial Violence in Canada - Roots, Katrin (Anti-Trafficking Review, 2019)
In Responding to Human Trafficking: Dispossession, Colonial Violence, and Resistance among Indigenous and Racialized Women, Julie Kaye offers a critical examination of how Canadian state and non-state actors understand human trafficking and implement anti-trafficking measures. Kaye examines Canada’s anti-trafficking policies and the efforts of non-government organisations (NGOs) through one-on-one interviews and focus group discussions. She demonstrates the way in which this politically charged issue has worked to conceal Canada’s violent colonial history and naturalise the inequalities and structural and material conditions in which trafficking and various forms of violence occur. Kaye argues that trafficking discourses position the colonial state as the saviour and therefore work to reinforce its power.